An Examination of the Hadith of Hind: The question of Provision for Family in Islamic Jurisprudence - Muhammad Ali Gibran Al Zuraib (Journal for ReAttach Therapy and Developmental Diversities, 2023)
This study focuses on the stylistic peculiarities, lexical meanings and structures of the language used in the Quran as the source of law. It analyzes words and sentences of the revelation in order to extract the most significant insights contained within the prophetic text. More specifically, this study explores the jurisprudential provision which can be induced from the Hadith of Hind bint `Utba. Findings confirm that the Prophet (PBUH) was endowed with the most eloquent and pithy expressions. Additionally, the analysis highlights the abundance of practical jurisprudential applications within the legal texts. The study summarizes previous, similar studies and establishes the significance and objectives of the current study in the light of these earlier findings. It carries out detailed analysis of the original Hind bint `Utba's Hadith text from which the provisions were derived, and presents its different interpretations and explanations. In addition to this, the study provides an overall explanation of the hadith and its associated benefits. Finally, it devotes a section to the benefits derived from the Hind's Hadith which is also the core of the research here and the legal provisions deduced by jurists therefrom. Lastly, the conclusions summarize the researcher's findings for the benefit of future theological and legal studies and research. Keywords: Hind bint `Utba, provision, scarce winning the right.